Phosphorus solubilizing microorganisms: potential promoters of agricultural and environmental engineering - Wang, Chengdong; Pan, Guojun; Lu, Xin; Qi, Weicong (Frontiers in Bioengineering and Biotechnology, 2023)
Phosphate solubilizing microorganisms (PSMs) are known as bacteria or fungi that make insoluble phosphorus in soil available to plants. To date, as beneficial microbes, studies on PSMs indicated they have potential applications in agriculture, environmental engineering, bioremediation, and biotechnology. Currently high cost and competition from local microbe are the most important factors hindering PSMs commercialization and application as for instance biofertilizer, soil conditioner or remediation agent etc. There are several technical strategies can be engaged to approach the solutions of these issues, for instance mass production, advance soil preparation, genetic engineering etc. On the other hand, further studies are needed to improve the efficiency and effectiveness of PSMs in solubilizing phosphates, promoting plant growth, soil remediation preferably. Hopefully, PSMs are going to be developed into ecofriendly tools for sustainable agriculture, environment protection and management in the future.